2017
DOI: 10.18203/2320-6012.ijrms20171811
|View full text |Cite
|
Sign up to set email alerts
|

Gender based knowledge, attitude and practice study about blood donation among medical students in a sub-Himalayan state

Abstract: Background: WHO is advocating a policy towards 100% voluntary non-remunerated blood donation by year 2020. The youth in general and medical students in particular constitute the core group for recruitment and retention of voluntary donor population in order to ensure safe and sustainable blood transfusion practices in India. The objective of the present study is to elucidate the knowledge, attitude and practices about voluntary blood donation among medical undergraduate students.Methods: A pretested, close end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Blood can only be gained from generous donors [ 7 ]. Youths, particularly medical students, constitute the core group for recruitment and retention of voluntary donor populations to ensure safe and sustainable blood transfusion [ 8 , 9 ]. The process of blood donation (BD) is affected by several factors, among which people´s level of knowledge and attitude are the key determinants [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood can only be gained from generous donors [ 7 ]. Youths, particularly medical students, constitute the core group for recruitment and retention of voluntary donor populations to ensure safe and sustainable blood transfusion [ 8 , 9 ]. The process of blood donation (BD) is affected by several factors, among which people´s level of knowledge and attitude are the key determinants [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies conducted Worldwide regarding knowledge and attitude towards blood donation revealed that 48.2% and 79.2% in Gondar [ 13 ], 40.4% and 47.4% in Ambo [ 9 ], 54% and 65.8% in Samara [ 5 ], 82.6% and 58.7% in Woliyta Sodo [ 7 ], 56.8% and 82% in Gondar [ 14 ], 43.5% and 32.9% in Harar [ 15 ] studies in Ethiopia, 66.7% and 68.7% in Saudi Arabia [ 16 ], 97.1% and 88.8% in Malaysia [ 17 ], 98% and 67% in Pakistan [ 18 ] and 15.5% and 17.69% in Iran [ 2 ] of the respondents had good knowledge and positive attitude towards blood donation respectively. The factors that affect the level of knowledge and attitude towards blood donation are varied from region to region based on deference´s in age, gender, residence, academic year, parent education and experience of blood donation [ 2 , 8 - 10 , 15 , 17 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The previously conducted studies in different parts showed that the magnitude of blood donation practice range from 10% to 35.69% in Asia 14–16 and 10.64% to 61.69% in Africa 11 , 17 , 18 which was relatively incomparable with high-income countries. It was found to be 29% in Saudi Arabia, 19 26.7% in India, 20 27.1% in Ghana, 21 15.3% in Nigeria 22 and 22.6%–47.8%, 5 23–28 in different regions of Ethiopia. On top of this, various factors are identified as the factors that hinder blood donation practice.…”
Section: Introductionmentioning
confidence: 97%